Nepālako nayām Saṃvidhāna ra Pañcāyata : hālasammako saṃśodhana-sahita, 2040 - Śarmā, Je (Vināyaka Pustaka Kendra, 1983)
On the Nepal's Constitution, as amended up to 1983, and the National Panchayat.